2007
DOI: 10.1007/s10528-006-9051-0
|View full text |Cite
|
Sign up to set email alerts
|

Population Structure of Wild Musk Shrews (Suncus murinus) in Asia Based on Mitochondrial DNA Variation, with Research in Cambodia and Bhutan

Abstract: The musk shrew (Suncus murinus) is a small mammalian species belonging to Insectivora. It is widely distributed in Asia. To identify the genetic relationship among wild musk shrew populations and examine its migration route, we investigated the populations of Cambodia and Bhutan by using mitochondrial DNA restriction fragment length polymorphism analysis and compared them with other Asian populations previously described. Four haplotypes were detected in Cambodia and eight in Bhutan. A total of 53 haplotypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Despite the monomorphic nature observed in this study, these 96 markers may be useful in population and other genetic studies of S. murinus, because successful PCR amplification was achieved in the three strains (TKU, BAN-kc,oeb and WZ). Their utility in these studies will complement work already done with mitochondria DNA [15,39,40], biochemical variants [33], morphometric parameters [11] and vitamin D binding protein [6]. All the 58 loci with clear alleles exhibited the co-dominant mode of inheritance.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Despite the monomorphic nature observed in this study, these 96 markers may be useful in population and other genetic studies of S. murinus, because successful PCR amplification was achieved in the three strains (TKU, BAN-kc,oeb and WZ). Their utility in these studies will complement work already done with mitochondria DNA [15,39,40], biochemical variants [33], morphometric parameters [11] and vitamin D binding protein [6]. All the 58 loci with clear alleles exhibited the co-dominant mode of inheritance.…”
mentioning
confidence: 76%
“…The microsatellite markers developed in this study should be a valuable resource for molecular genetic studies, population genetics, and so on. [15].…”
mentioning
confidence: 99%
“…We speculate that the V240A variation developed after the separation of ancestral wild suncus into geographically distant regions. A phylogenetic tree deduced from the sequence of mitochondrial DNA control regions classifies KAT and RYU (OKI:Okinawa) into continental and insular groups [21], and indicates the substantial distance between KAT and RYU. The several variations in TYR identified between KAT and RYU strains, as well as the V240A variation in SLC45A2, may be used to elucidate how wild suncus segregated in different regions of Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, wild musk shrew populations in Asia, including those in Nepal, Bhutan, Bangladesh, Sri Lanka, Myanmar, Thailand, Malaysia, Indonesia, the Philippines, Vietnam, Cambodia, Japan, and Mauritius, were investigated based on mitochondrial DNA (mtDNA) restriction fragment length polymorphism (RFLP) analysis (Yamagata et al 1995(Yamagata et al , 1999(Yamagata et al , 2004Kurachi et al 2007). These studies revealed two largely different types of mtDNA, Continental and Island.…”
Section: Introductionmentioning
confidence: 99%
“…After an investigation of the Myanmar, Cambodia, and Bhutan populations, the possibility of partial migration routes was supported (Kurachi et al 2007). However, these routes are merely hypothetical, because the shrews in South India, which is the primary region, where the migration route and the evolutionary process of wild musk shrews can be confirmed, have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%